Urgensi Peta Dakwah - Rohmanur Aziz (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
The existence of religious activity in society can not be separated from activities that are the rituals, routines are conducted in accordance religious agenda each and there are social activities that are more flexible with the time scheduled by the will of the people. The function of religious activities is to realize the servitude of man as a creature to his Lord by running various rules and religious guidance. The position of religion must be understood as the representation of the will of God revealed in scripture through the intermediary of the Prophets and Messengers as a messenger of God. The function of these religious activities which in turn drive the human civilization both worldly materialistic nature (world view) and the nature of eschatological things.